2018
DOI: 10.21037/atm.2018.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Tumor progression: the neuronal input

Abstract: One of the challenges of cancer is its heterogeneity and rapid capacity to adapt. Notwithstanding significant progress in the last decades in genomics and precision medicine, new molecular targets and therapies appear highly necessary. One way to approach this complex problem is to consider cancer in the context of its cellular and molecular microenvironment, which includes nerves. The peripheral nerves, the topic of this review, modulate the biological behavior of the cancer cells and influence tumor progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 131 publications
0
44
0
Order By: Relevance
“…Organisms are continuously exposed to a variety of stresses that cause maladaptation and can even lead to cancer. In addition to changes in humoral immunity, recent studies have shown that the peripheral nerves in TNCs are associated with stress‐induced physiological changes in cancer cells (Arese et al , 2018; Faulkner et al , 2019; Jobling et al , 2015; Magnon, 2015; Mauffrey et al , 2019; Tang et al , 2013). Neurotransmitters are age‐old secreted modulators that are evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organisms are continuously exposed to a variety of stresses that cause maladaptation and can even lead to cancer. In addition to changes in humoral immunity, recent studies have shown that the peripheral nerves in TNCs are associated with stress‐induced physiological changes in cancer cells (Arese et al , 2018; Faulkner et al , 2019; Jobling et al , 2015; Magnon, 2015; Mauffrey et al , 2019; Tang et al , 2013). Neurotransmitters are age‐old secreted modulators that are evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is a commonly occurring cancer that is densely innervated by autonomic fibers and results in shortened patient survival (Liebl et al , 2013). TNCs consist of sympathetic and parasympathetic nervous system (Arese et al , 2018; Faulkner et al , 2019; Jobling et al , 2015). Activation of the adrenergic system significantly affects stress‐induced cancer progression (Magnon et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, new therapeutic algorithms and strategies are needed for better PC control. Although the true impact of microenvironment in PC pathogenesis and progression is not known, it is clear that targeting the stromal components may represent a promising approach for the treatment of PC [17,52].…”
Section: Pc Pathoclinical Datamentioning
confidence: 99%
“…The other related topics are molecules involved in tumor-neural TME interactions, with 3 main classes of proteins: neurotrophic factors, axon guidance molecules and NT including neuropeptides. Their sources are cancer cells, tumor-associated neuroendocrine Pathobiology 2020;87:87-99 DOI: 10.1159/000505437 cells, and stromal elements [17]. Experiments on PC cell lines showed that PC androgen-resistant cell culture have their genetic profile consistent with the socalled brain signature in 28% [51].…”
Section: Pc Stroma and Its Neural Componentmentioning
confidence: 99%
See 1 more Smart Citation